Applied differential equations the primary course - Dobrushkin, V. A. (Vladimir Andreevich) (Textbooks in mathematics, 2015)
Introduction -- First order equations -- Numericals methods -- Second and higher order linear differential equations -- Laplace transforms -- Introduction of systems of ODEs -- Topics from linear algebra -- Systems of linear differential equations -- Qualitative theory of differential equations -- Orthogonal expansions -- Partial differential equations